Rancang Bangun Sistem Informasi KKN UNP Berbasis Web Menggunakan Framework Codeigniter - Aziz, Muhamamd Haikal; Tasrif, Elfi (Universitas Negeri Padang, 2022)
KKN UNP is a unit for implementing real work lectures at UNP that must be committed to supporting the development of UNP in the future. Kuliah Kerja Nyata (KKN) is one of the activities that must be carried out by every student at Padang State University as a real form of community service. The purpose of this research is to produce an information system that can overcome the KKN registration process, distribution of supervisors, assessment of student KKN implementation, and become a means of information related to KKN. The result of this design is to produce a system that can improve service and management of KKN, as well as expedite the administrative process. This system is designed using Context Diagrams, User Case Diagrams, Activity Diagrams, Entity Relation Diagrams, Normalization, and is built using the PHP programming language with the Codeigniter framework, MySQL as a DBMS. The result of this final project is a UNP KKN Information System that will assist the process of implementing KKN activities at UNP.